2019
DOI: 10.5424/sjar/2019173-14938
|View full text |Cite
|
Sign up to set email alerts
|

Effects of white shrimp (Litopenaeus vannamei) and tilapia nilotica (Oreochromis niloticus var. Spring) in monoculture and co-culture systems on water quality variables and production in brackish low-salinity water earthen ponds during rainy and dry seasons

Abstract: Aim of study: To determine the effects of white shrimp (Litopenaeus vannamei) and tilapia nilotica (Oreochromis niloticus var. Spring) in monoculture and co-culture on water quality variables and production in earthen ponds during dry and rainy seasons.Area of study: A shrimp farm (total area 20 ha) at Chiripa, San Blas Nayarit, Northwest coast of Mexico (21° 37' 34.53 " N; 105° 18' 16.31" W).Material and methods: Two production cycles were performed in a completely randomized design consisting of two treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 25 publications
1
2
0
3
Order By: Relevance
“…The variables of temperature, pH and DO during the experiment were within the appropriate intervals for the growth of tilapia and shrimp in monoculture and polyculture. The concentration of TN and TP showed no significant differences among different culture systems in this study, which was in agreement with the findings of Juárez‐Rosales et al, (2019) who recorded the same TN and TP between monoculture and polyculture system. NH4+0.333333em- N in water originates from the faeces and excessive feed, damages the gills, increases oxygen consumption and affects shrimp growth (Chen & Kou, 1992).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The variables of temperature, pH and DO during the experiment were within the appropriate intervals for the growth of tilapia and shrimp in monoculture and polyculture. The concentration of TN and TP showed no significant differences among different culture systems in this study, which was in agreement with the findings of Juárez‐Rosales et al, (2019) who recorded the same TN and TP between monoculture and polyculture system. NH4+0.333333em- N in water originates from the faeces and excessive feed, damages the gills, increases oxygen consumption and affects shrimp growth (Chen & Kou, 1992).…”
Section: Discussionsupporting
confidence: 93%
“…The bulk of studies indicate that polyculture systems can influence the growth and yield of aquatic organisms (Fitzsimmons & Shahkar, 2017; Juárez‐Rosales et al, 2019; Ribeiro et al, 2012; Yuvaraj et al, 2009). The co‐culture ponds of shrimp and tilapia ( Oreochromis niloticus ) displayed higher biomass of the shrimp than those of the shrimp monoculture (Juárez‐Rosales et al, 2019). Polyculture Litopenaeus stylirostris and Siganus lineatus can also significantly increase total yield Luong et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Improving pond water quality by controlling phytoplankton growth, reducing the accumulation of organic matter, antibacterial effect and the prevalence of viruses (Jatobá et al, 2011). Juarez-Rosales et al (2019) reported that the white shrimp (10 org/m 2 ) can be co-cultured with Nile tilapia at a stocking high density (4 org/m 2 ), leading to improved water quality.…”
Section: Physical Water Parametersmentioning
confidence: 99%
“…Estos beneficios se han logrado en los tres sistemas de co-cultivo conocidos (directo, en jaula y en co-cultivo integrado); otros autores resumen las ventajas en la disminución de los impactos ecológicos, las mejoras en el rendimiento y en la calidad del agua (24); de manera más específica y bajo determinadas condiciones, favorece la retención de nutrientes y disminuye de manera importante el nitrógeno que generan los cultivos acuícolas (1,28). La tilapia al cultivarla con camarones, juega un rol importante en la reducción de la biomasa de fitoplancton y promueve microalgas biorremediadoras (25).…”
Section: Calidad Del Agua Y Sedimentos En Estanques De Policultivounclassified
“…En estudios se ha encontrado que es menor la diferencias en la sobrevivencia de la tilapia en monocultivo (84-87.6%) y policultivo (91.2-100%) en estanques de tierra (24). Los estanques de tierra naturales con aguas de alta calidad y baja salinidad permiten la sostenibilidad de una mayor densidad de población de tilapia (4 org/m 2 ) que los sistemas (Tabla 2) o estanques que carecen de sustrato (1.2 org/m 2 ) en el fondo (tanques de fibra de vidrio o cemento) (tabla 2) (24). En términos generales el policultivo tilapia-camarón tiene mayores ventajas técnicas en cultivos extensivos y semi-intensivos a nivel comercial.…”
Section: Aspectos Técnicos Del Policultivo Camarón-tilapiaunclassified